Multi-Tasking on Chromatin with the Saga Coactivator Complexes - Daniel, Jeremy A. (2007)
Over the past ten years, much progress has been made to understand the roles of the similar, yet distinct yeast SAGA and SLIK coactivator complexes involved in histone post-translational modification and gene regulation. Many different groups have elucidated functions of the SAGA complexes including identification of novel components, which have conferred additional distinct functions. Together, recent studies demonstrate unique attributes of the SAGA coactivator complexes in histone acetylation, methylation, phosphorylation, and deubiquitination. In addition to roles in transcriptional activation with the 19S proteasome regulatory particle, recent evidence also suggests functions for SAGA in elongation and mRNA export. The modular nature of SAGA allows this ∼1.8MDa complex to organize its functions and carry out multiple roles during transcription, particularly under conditions of cellular stress.